Teaching English to Junior High School: A Focus on Problems and Solutions - Maghfirah, Maghfirah; Samad, Iskandar Abdul; Fitrisia, Dohra (UNIB Press, 2025)
This research aims to identify the problems faced by English teachers and solutions applied in teaching at junior high schools. This study employs a mixed method approach, combining both quantitative and qualitative methodologies in a complementary manner. The quantitative approach was conducted through questionnaires distributed to 32 respondents from 23 junior high schools, while the qualitative approach involved in-depth interviews to gain deeper insights. Quantitative data were analyzed using descriptive statistical analysis, while qualitative data were analyzed using thematic analysis. The results of the study show that teachers face various problems, including limited textbooks, inadequate educational facilities, challenges in developing competencies, and differences in abilities among students. To address these issues, teachers implement a variety of solutions, such as seeking additional teaching materials, using personal facilities, attending online training, and adopting a differentiated approach in teaching. The conclusion of this study highlights the importance of greater support for teachers in the form of providing adequate facilities, professional development, and cooperation with parents and the community to improve the quality of English language learning in junior high schools.